European social policy and social work : citizenship-based social work. - van Ewijk, Hans, 1947- (London : Routledge, 2010)
European Social Policy and Social Work explores shifts in international social policies and how they affect national trends and thus the context for social work practice. The book discusses international and national social work strategies and practice and investigates the responsibilities for social welfare held by the state, the market and civil society. Hans van Ewijk then elaborates a new concept of citizenship-based social work which supports and encourages self-responsibility, social responsibility and the implementation of social rights. The main themes covered are: - international social policy and social work - from welfare to workfare - citizenship - essentials of citizenship based social work - community policy and community work - social work and alternative areas of activity such as youth care and social care Integrating different roots and social professions in an overarching new concept, this book particularly looks at European Union countries. Hans van Ewijk examines debates regarding social work as an internationally recognised profession and science. This book is suitable for social work students, academics and professionals with an interest in social policy and international social work.
Keywords: Go international; International office; Sociaal werk